2009
DOI: 10.1177/000312240907400407
|View full text |Cite
|
Sign up to set email alerts
|

All the Movements Fit to Print: Who, What, When, Where, and Why SMO Families Appeared in the New York Times in the Twentieth Century

Abstract: Why did some social movement organization (SMO) families receive extensive media coverage? In this article, we elaborate and appraise four core arguments in the literature on movements and their consequences: disruption, resource mobilization, political partisanship, and whether a movement benefits from an enforced policy. Our fuzzy-set qualitative comparative analyses (fsQCA) draw on new, unique data from the New York Times across the twentieth century on more than 1,200 SMOs and 34 SMO families. At the SMO f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 50 publications
2
101
0
Order By: Relevance
“…the number of participants) (Barranco and Wisler 1999;McCarthy et al 1996;Mueller 1997a;Oliver and Myers 1999;Fillieule 1998;McCarthy et al 2008;Herkenrath and Knoll 2011); (2) the geographic distance between the event and the media source, especially its reporting market and audience (Barranco and Wisler 1999;Hocke 1998;McCarthy et al 1996;Mueller 1997a;Fillieule 1998;Strawn 2008;Herkenrath and Knoll 2011); (3) Paralleling these general patterns for events, Amenta et al (2009) find that New York Times mentions of social movement families are greater for larger, better organized and disruptive movements that use protest and those with an enforced governmental policy in place. They also find that the power of partisan allies does not influence selection.…”
Section: Regional Newspaper Reportage In Mexicomentioning
confidence: 96%
“…the number of participants) (Barranco and Wisler 1999;McCarthy et al 1996;Mueller 1997a;Oliver and Myers 1999;Fillieule 1998;McCarthy et al 2008;Herkenrath and Knoll 2011); (2) the geographic distance between the event and the media source, especially its reporting market and audience (Barranco and Wisler 1999;Hocke 1998;McCarthy et al 1996;Mueller 1997a;Fillieule 1998;Strawn 2008;Herkenrath and Knoll 2011); (3) Paralleling these general patterns for events, Amenta et al (2009) find that New York Times mentions of social movement families are greater for larger, better organized and disruptive movements that use protest and those with an enforced governmental policy in place. They also find that the power of partisan allies does not influence selection.…”
Section: Regional Newspaper Reportage In Mexicomentioning
confidence: 96%
“…The media's coverage of a movement is largely dependent upon political context and a myriad of other variables such as type of protest, size of protest, and fickle media attention cycles. Not all movements are likely to receive coverage equally, if they receive any at all [2,[39][40][41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, a large body of research has demonstrated that the media actually tends to work against social movements by distorting their message or otherwise casting them in an unfavorable light (Amenta et al 2009;Gamson et al 1992;McCarthy et al 1996;Oliver and Maney 2000). That is, movements usually do not enjoy the power to frame their message to their liking in elite-controlled spaces.…”
Section: Social Movements Media and Motivationmentioning
confidence: 99%